English Language Anxiety in Adult Learners: Challenges and Opportunities - Hossain, Kazi Imran; Ahmed, Ilias; Mahmud, Md Sabid (IUBAT Review, 2023)
English language anxiety (ELA) is an issue among adults who are learning a language. It affects their experience and outcomes in language learning. This comprehensive review explores the nature of ELA, examining its aspects and implications for language instruction. The research investigates how the classroom environment, linguistic challenges, academic performance, communication difficulties, emotional well-being, motivation, and other personal and societal factors contribute to ELA. It also delves into the role of technology, self-reflection, and training in English language acquisition. The review emphasises the importance of creating inclusive language learning spaces, providing teacher training programmes, and encouraging self-practice to address English Language Anxiety (ELA). Moreover, evidence-based solutions such as task design and tolerance for errors are recommended to help students overcome ELA and enhance their overall language learning experience. The conclusions and suggestions presented in this review can be valuable for adult learners of languages who seek to understand and engage with individuals from diverse cultures. IUBAT Review, 6(2): 158-183